Stuxnet Recruits the Proteasome to Take Down Polycomb. - Karch, F. (Developmental Cell, 2016)
In this issue of Developmental Cell, Du et al. (2016) describe a gene named stuxnet that regulates Polycomb protein stability, thereby influencing the activity of the Polycomb-group repressive chromatin complexes.